Pengaruh Time Token Arends Terhadap Kemampuan Berpikir Kritis Mata Pelajaran IPS Kelas V - Fadil, Khaidir Fadil; Fitriani, Destia; Iktiono, Gunawan (azkiya, 2023)
The low level of critical thinking skills is partly due to the lack of involvement of students in the learning process so that they do not have the opportunity to have an opinion. The purpose of this study was to determine the effect of the time token learning model on students' critical thinking skills in social studies class V MI Mathla'ul Anwar Cibitung Tengah. This research is included in Quantitative research with the type of research Quasi experiment. This research design uses Nonequivalent Control Group design with purposive sampling technique. The sample of this study used 70 grade V students of MI Mathla'ul Anwar Cibitung Tengah where VA amounted to 40 students as an experimental class using the time token learning model and VB class amounted to 30 as a control class using the direct learning model. Data collection techniques using observation, tests and documentation. The results showed that there was a significant effect on the use of the time token learning model on students' critical thinking skills in social studies subjects in the VA class of MI Mathla'ul Anwar Cibitung Tengah, this was evidenced by the results of the Posttest test in the experimental class which was 75.75 while in the control class 66. So it can be concluded that there is a significant influence on students' critical thinking skills between the application of a cooperative learning model in the form of time tokens and the application of a direct learning model for fifth grade students in social studies.